Environmental Regulation and Compulsory Public Disclosure. - Afsah, Shakeb (Environment for development., 2013)
This book is a remarkable case study of an environmental policy initiative for a national environmental regulatory system in the information age. In 1995 the Indonesian Ministry of Environment took the bold step to launch an environmental disclosure initiative called the Program for Pollution Control, Evaluation and Rating (PROPER). Under PROPER, environmental performance of companies is mapped into a five-color grading scale - Gold for excellent, Green for very good, Blue for good, Red for non-compliance, and Black for causing environmental damage. These ratings are then publicly disclosed.